Concrete Technology Competency Training with Blended Learning and Flipped Clasroom Learning Models: Pelatihan Kompetensi Teknologi Beton dengan model pembelajaran Blended Learning dan Flipped Clasroom - Milyardi, Roi; Kristianto, Anang; Tangkelayu, Nathaniel Reinhart (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Concrete technology competency training is a primary factor in the construction industry with the challenges of technological development. The Covid-19 pandemic period is a challenge in the training in adapting training methods. Concrete Technology Laboratory organizes community service for concrete technology competency training by utilizing Blended Learning (BL) and Flipped Clasroom (FC) learning models to meet these needs and challenges. The training participants totaled 11 people with various professional backgrounds in the construction world. Indicators of the success of community service methods are measured through pre-test, post-test, and activity evaluation surveys. From the results of the pre-test and post-test, community service activities provide a high level of success, indicated by the trend of increasing test scores, as well as the acceleration of participants' test time. The application of BL and FC learning models in community service provides the effectiveness of positive training achievements in the challenges of the Covid-19 pandemic.